Asean paradox and the state-ship In Southeast Asian regionalism - Xu, Shuzhan (2016)
First, ASEAN is a unique product that born and develop in the unique history of Southeast Asia. Though the experience of the EU regionalism and western normative are overwhelmingly influential, the study of ASEAN must be based on the region. Second, ASEAN is state centric, however, not state only. The ASEAN Way and conspicuous role of state in the ASEAN is a fruit of the unique history of Southeast Asia. ASEAN was designed to provide national building, rather than regional. Third, ASEAN economic regionalism was initiated for the construction of an integrated market to attract FDl to fill the national economy. However, the prominent role of state in the regional economy makes the “ASEAN Way” important in the economic cooperation thus the AEC are created not as a free flowing market, instead, as one market carefully sustained by states.